Essays on International trade and economic growth (2015)
At present, we are witnessing globalization as a truly worldwide phenomenon. Trade agreements among differing countries, a reduction in trade costs, the mobility of production factors, the free flow of information and so on are all proof of the present day era of globalization. Countries are trading with one another more and more every day and the effects of international trade on economies represent a central discussion in all economic spheres. In spite of increasing trade around the world and the promotion of globalization by multilateral organisms such as WTO and IMF, the effects of international trade are not yet clear. Economics literature concerning the effects of international trade on economic growth and welfare remains ambiguous in terms of both theoretical models and empirical research. The present thesis tries to contribute to the theoretical debate surrounding the effects of dynamic international trade, focusing in particular on the implications for economic growth, welfare and changes in the preferences of individuals.